The Availability of Electronic Courses Using ICT Infrastructure in Teaching and Learning among Teachers in Nigeria's TVET Institutions. - Mohd Hashim, M. H.; Abubakar, B. (Pertanika Journal of Social Sciences & Humanities)
As information and communication technology becomes a regular feature of the educational environment, it may be difficult for teaching and learning activities especially in TVET institutions to remain unchallenged. However, ICT application as a pedagogical tool in Nigerian TVET institutions is not a common practice and it also remains unclear how utilisation of ICT enhances pedagogy. This study is interested in the availability of electronic courses using ICT infrastructure in teaching and learning. Using activity theory as a guide, multiple case studies are conducted. The Qualitative Case Study Methodology is used in this research. Five TVET institutions and 20 participants are selected using maximum variation and homogeneous purposive sampling strategies, respectively. During the visits to the institutions, classroom observation is carried out, documents such as the curriculum and teacher's lecture materials are reviewed for triangulation. Semi-structured interviews are conducted with 20 selected participants as the primary data collection method. At the data analysis stage, the inductive and deductive methods are used to analyse the data and two strategies of grounded theory as open and axial coding are employed. The coding process is achieved through the use of an inherent feature of NViVOlO. The findings show that four themes: availability of infrastructure, computer specifications, educational software and connectivity.